2017
DOI: 10.1371/journal.pone.0169900
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Multi-Drug Resistant Pathogens and Failure of Empiric First-Line Therapy in Acute Cholangitis

Abstract: BackgroundAcute cholangitis (AC) requires the immediate initiation of antibiotic therapy in addition to treatment for biliary obstruction. Against a background of an increasing prevalence of multi-drug resistant (MDR) bacteria, the risk factors for the failure of empiric therapy must be defined.MethodsUsing a pathogen-based approach, 1764 isolates from positive bile duct cultures were retrospectively analyzed to characterize the respective pathogen spectra in two German tertiary centers. Using a patient-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
3
40
0
2
Order By: Relevance
“…Anaerobes were detected in less than 10% of our patients. These results are consistent with other recent reports [7][8][9][10] and revise the classic view that both enterobacterales and anaerobes are the most important pathogens in biliary tract infections [11]. Bacteremia was detected in one third of cases with available blood culture results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Anaerobes were detected in less than 10% of our patients. These results are consistent with other recent reports [7][8][9][10] and revise the classic view that both enterobacterales and anaerobes are the most important pathogens in biliary tract infections [11]. Bacteremia was detected in one third of cases with available blood culture results.…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiological data from Germany suggest a frequency of 3GCRE of about 15% in hospitals [14]. In an analysis of cholangitis cases from two other German university hospitals, ESBL producing E.coli were detected at a rate of 31% [10]. In our cohort, the highest numbers of cholangitis associated with either 3GCRE or MRGN (See figure on previous page.)…”
Section: Discussionmentioning
confidence: 59%
“…There is a lack of clinical trials examining the benefit of blood cultures in patients with acute biliary tract infections. On the other hand, there is an argument that every opportunity should be used to identify microorganisms and susceptibility testing in the era of antimicrobial resistance .…”
Section: Clinical Questionsmentioning
confidence: 99%
“…A prospective cohort study in patients with acute cholecystitis involving 116 institutions worldwide showed that among 96 isolated E. coli , 16 (16.7%) were producing ESBL . However, the proportion of ESBL producing E. coli varies widely region to region: 31.2% in two German university hospitals , 70.0% in Korean university medical center and 66% in Indian medical college hospital . There are few reports about the prevalence of carbapenem resistant bacteria specifically among patients with acute cholangitis and cholecystitis.…”
Section: Introductionmentioning
confidence: 99%
“…Zwei Folgestudien konnten ebenfalls nicht eindeutig die Wirksamkeit dieser Maßnahmen nachweisen: Während eine Studie unter der Kombination von UDCA mit Levofloxacin eine niedrige Rate an Stentokklusionen und Cholangitiden fand [120], wurde in einer doppelblinden randomisierten Studie mit Ciprofloxacin bei 94 Patienten eine grenzwertig signifikante Abnahme der Cholangitishäufigkeit von 42 auf 21 % beobachtet [121]. Retrospektive infektiologische Untersuchungen weisen darauf hin, dass Patienten mit biliären Stents, die eine akute Cholangitis entwickeln, eine empirische Antibiotikatherapie, die Enterokokken und Extended spectrum β-Laktamasen (ESBL) -bildende Enterobakterien abdeckt, erhalten sollten [122].…”
Section: Kommentarunclassified